The Value of Independent Character Education In Surah Al-Insyirah - achyar zein; Edi Saputra; Fahrul Ulum Feriawan (At-Tarbiyat, 2021)
This study examines the concept of independent character education in surah al-Insyirah, the values of self-education in surah al-Insyirah, and the relevance of the value of independent education in surah al-Insyirah to contemporary education. This research uses a qualitative method, using a library research approach. The primary data source in this study is the Qur'an al-Karim along with the books of interpretation, such asTafsir Al-Misbah, Tafsir Al-Wasith, Tafsir Jalalain, Tafsir Muyassar, and Tafsir al-Maraghi. The results show thatthe concept of self-education in surah al-Insyirah briefly contains aboutdetails of God's blessings to his prophet, God's promise to His prophet to eliminate all disasters and trials that befall him, God's command to His prophet to carry out the deeds of soleh continuously, putting histrust in God and expectreward only from God. The Values of Self-Education in Surah al-Insyirah are Grateful for the Blessings of Allah Swt (1-4), Do Not Despair (5-6), Istiqomah (7), and Tawakkal (8), and the relevance of Independent Education Values in Surah al-Insyirah to contemporary education are the values of education is an independent education that should be instilled by parents to their children early so that the child will become an independent character, both at home and at school and will bring such an independent attitude until he getsold.